Defect‐Dependent Crystal Plane Control on Inorganic CsPbBr3 Film by Selectively Anchoring (Pseudo‐) Halide Anions for 1.650 V Voltage Perovskite Solar Cells. (21st July 2022) - Zhu, Jingwei; He, Benlin; Zhang, Wenyu; Tui, Rui; Chen, Haiyan; Duan, Yanyan; Huang, Hao; Duan, Jialong; Tang, Qunwei
Abstract: One of the key problems to improving the performance of a typical perovskite solar cell (PSC) is to minimize the defect‐determined nonradiative recombination. So far, the cutting‐edge strategies mainly focus on the film‐scale defect manipulation at grain boundaries and surfaces by trial‐and‐error, but the intrinsic passivation mechanism and fundamental guideline in the perspective of crystal lattices are still unclear. Herein, a much lower defect formation energy of PbBr antisite defect at (110) plane than that at (h00) planes is demonstrated by theoretically studying the crystal plane‐dependent defect density in an inorganic CsPbBr3 film, and then the authors precisely control the plane growth by selectively anchoring (pseudo‐) halide anions from ionic liquids to (110) plane. Because of the different adsorption energies on various planes, the growth of defective (110) plane is suppressed, leading to the formation of (h00) plane‐oriented film. Finally, the all‐inorganic CsPbBr3 PSC passivated by ionic liquid EMImCl delivers the best efficiency of 10.71% with an open‐circuit voltage up to 1.650 V. This work provides an in‐depth insight into defect formation and passivation mechanism to stabilize perovskite photovoltaics. Abstract : Theoretical study demonstrates the defective (110) crystal plane is terminated by selectively anchoring (pseudo‐) halide anions, and a champion efficiency up to 10.71% with a voltage of 1.650 V is achieved in the all‐inorganic CsPbBr3 perovskite solar cell.